(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Mood is a complex, multifaceted psychological construct that significantly influences human behavior, cognition, and interpersonal relationships. This article investigates the universal nature of mood, emphasizing its definitions, cultural variations, and implications for mental health. Through a comparative analysis of diverse cultural perspectives, we highlight how mood is expressed and understood, underlining its relevance in psychological research and clinical practice.